2007
DOI: 10.1007/s10661-007-9813-0
|View full text |Cite
|
Sign up to set email alerts
|

A western gray whale mitigation and monitoring program for a 3-D seismic survey, Sakhalin Island, Russia

Abstract: The introduction of anthropogenic sounds into the marine environment can impact some marine mammals. Impacts can be greatly reduced if appropriate mitigation measures and monitoring are implemented. This paper concerns such measures undertaken by Exxon Neftegas Limited, as operator of the Sakhalin-1 Consortium, during the Odoptu 3-D seismic survey conducted during 17 August’ September 2001. The key environmental issue was protection of the critically endangered western gray whale ( Eschrichtius rob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 15 publications
(13 reference statements)
0
29
0
1
Order By: Relevance
“…To minimize the impacts of such activity on the whales, several mitigation and monitoring plans (MMP) have been implemented targeting specific activities, such as seismic surveys, platform installation, dredging and pipeline placement (Johnson et al 2007, SEIC 2005, 2006. Despite efforts to reduce overall sound exposure levels, responses by the whales were observed, including changes in distribution and behaviour (Weller et al 2002,b, 2010, Yazvenko 2007a.…”
Section: Introductionmentioning
confidence: 99%
“…To minimize the impacts of such activity on the whales, several mitigation and monitoring plans (MMP) have been implemented targeting specific activities, such as seismic surveys, platform installation, dredging and pipeline placement (Johnson et al 2007, SEIC 2005, 2006. Despite efforts to reduce overall sound exposure levels, responses by the whales were observed, including changes in distribution and behaviour (Weller et al 2002,b, 2010, Yazvenko 2007a.…”
Section: Introductionmentioning
confidence: 99%
“…During the summer of 2001, 3D seismic surveys were conducted from 17 August to 9 September in prime gray whale foraging habitat (Odoptu) off Sakhalin Island (Johnson et al 2007). Systematic observations of whales in relation to operational condition (i.e.…”
Section: Case 5: Western Pacific Gray Whalesmentioning
confidence: 99%
“…Systematic observations of whales in relation to operational condition (i.e. pre-seismic, seismic, post-seismic) showed that a significantly lower number of individuals and groups were seen during seismic surveys, compared to pre-and post-seismic conditions (Weller et al 2006, Johnson et al 2007). This indicates a potential for harm caused by displacement of this endangered subpopulation from foraging areas (Weller et al 2006).…”
Section: Case 5: Western Pacific Gray Whalesmentioning
confidence: 99%
“…For example, the Exxon-Neftegas Limited (ENL) development in eastern Russia (Sakhalin-I) uses assets on shore to drill wells to reach and extract oil and gas from deposits 5 to 10 km offshore. It was nonetheless impossible for ENL to avoid its 2001 Odoptu 3-D seismic survey in support of the Sakhalin-I development (Johnson et al, 2007), and further 4-D seismic surveys of the Odoptu field will inevitably be required as the development proceeds.…”
Section: Pre-survey Planningmentioning
confidence: 99%